Atypical use of PICC as centrally inserted central catheter in infants and neonates: Report of a 10-year experience. Issue 3 (May 2023) - Nourzaie, Romman; Abbas, Hiba; Parthipun, Aneeta; Boolkah, Soo; Ahmed, Irfan; Gkoutzios, Panos; Moser, Steven; Monzon, Leonard; Karunanithy, Narayan; Diamantopoulos, Athanasios
Purpose: The aim was to determine the success, safety and post procedure complications of peripherally inserted central catheters as centrally inserted central catheters (CICC). Materials and method: One hundred and sixty-one consecutive infants and neonates, who underwent image guided tunnelled central venous catheter insertion were retrospectively evaluated between April 2008 and April 2018. Patient's demographics, site of access and procedure details were recorded. Outcomes included technical success and post procedure complications. Results: One hundred and eighty-two CICCs were inserted in 161 patients (49.7%, n = 80 male). Mean patient age was 100 days (range: 0–342) with a mean weight of 4.20 kg (range 1.80–9.40). The most common indication was for antibiotics administration (41%; n = 66). Technical success was 99% (181/182). Early complications (<7 days) were seen in 8.8% ( n = 13). This included inadvertent line removal in 5.5%, catheter-related bloodstream infection in 1.1% and catheter occlusion in 2.2% ( n = 4). Average line functional duration prior to removal was 26 days (range 0–180). 77.5% of the lines lasted for the intended duration of treatment. In the neonate subgroup, 84.1% (37/44 lines) of lines remained in situ for the intended duration of treatment. Conclusion: Tunnelled central venous catheters using non-cuffed peripherally inserted central catheters in infants is a safe technique with excellent success rate and minimal complications rates.